DETERMINAN PENGAMBILAN KEPUTUSAN DALAM PERENCANAAN PERSALINAN PADA KELAS IBU HAMIL - Fatimah Fatimah Fatimah; Sugeng Triyani Triyani; Aisyah Aisyah Aisyah (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Class of pregnant women means a group of pregnant women those learn about health of pregnant together. The members attend several meeting with midwifery to improve their knowledge and skills telated pregnancy topics, including childbirth, postpartum care, newborn care, myths, infectious diseases and birth certificates. In short, the class discusses and shares experiences among pregnant women and to health workers about the health of mother and child (Kesehatan Ibu dan Anak: KIA) themes. This study group activity called "Classes For Pregnant Women". Problem Summary: There are pregnant women who do not pass the class of 117 pregnant women (25%) and about 366 people outside the delivery area of 366 people found childbirth by herbalists for 42 people. Knowing the purpose of decision-making in planning determinant of labor in pregnant womenPopulation and sample: all pregnant women pregnant women class period August-September 2013 in the sub-district health centers Jatinegara. The study sample of 117 pregnant women with class participants. Research Method used analytical study design type cross sectional. Result analysis: Variables related, parity, education, knowledge, attitudes, frequency of visits and health personnel support. Suggestion: increase the formation of a new class of pregnant women to pregnancy can be monitored and parents can immediately take clinical decisions when the risk occurs.